2014
DOI: 10.1108/pr-10-2012-0176
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing employee satisfaction in the police service: the case of Slovenia

Abstract: PurposeThe paper has two purposes -first, to examine the dimensionality of employee satisfaction and, second, to identify the impact of the groups of factors on employee satisfaction. Design/methodology/approachThe measurement of satisfaction of all employees in the Slovenian Police based on the comprehensive on-line questionnaire. Factor analysis was used to formulate the facets of satisfaction. Multiple linear regression analysis was performed to identify the predictors of three facets of employee satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 43 publications
0
41
0
5
Order By: Relevance
“…• Company operations (company policies, work-family balance, support for diversity in the workplace, The company's grievance system's support of procedural and distributive justice, The number of control/autonomy employers (autonomy in decision making), Bureaucratic organisations, Meaningful work, A good physical work environment, Friendly co-workers, Work in which employees can excel , Competence of supervisor A person's feeling of satisfaction at work is influenced by factors that differ from one individual to another, such as personality, the influence of society, the situation in the workplace and values, according to Tomazevic, Seljak and Aristovnik (2014). According to Mullins (1996), some of the factors that have a major influence on job satisfaction are frustration and alienation, the nature of technology, meaningful work and the nature of supervision, work and psychological well-being, and stress at work.…”
Section: Influences On Job Satisfactionmentioning
confidence: 99%
“…• Company operations (company policies, work-family balance, support for diversity in the workplace, The company's grievance system's support of procedural and distributive justice, The number of control/autonomy employers (autonomy in decision making), Bureaucratic organisations, Meaningful work, A good physical work environment, Friendly co-workers, Work in which employees can excel , Competence of supervisor A person's feeling of satisfaction at work is influenced by factors that differ from one individual to another, such as personality, the influence of society, the situation in the workplace and values, according to Tomazevic, Seljak and Aristovnik (2014). According to Mullins (1996), some of the factors that have a major influence on job satisfaction are frustration and alienation, the nature of technology, meaningful work and the nature of supervision, work and psychological well-being, and stress at work.…”
Section: Influences On Job Satisfactionmentioning
confidence: 99%
“…It put forth that rewards, such as earnings, incentives, promotions, appreciation and opportunities for progress, can increase, improve and enhance the job satisfaction and motivation among employees (Taylor, ). Job satisfaction is affected by the work intensification of teachers and the societal trend for the overworking of teachers (Naylor, ), and must be looked at in the context of other key factors, such as general well‐being, quality of life, stress at work and in organisational matters, and a general feeling of control in one’s work and social life (Tomazevic et al , ). A significant aspect to research (Judge & Klinger, ) amongst Indian women in the education sector (Kumari et al , ) who were satisfied and motivated, was found to be dependent on the employees' personal well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in the second block after controlling for JC, CDP, COMM and SOCSUP, EE statistically contributed to an additional variance to the regression equation (R 2 = 0.118, p < 0.01); which showed an increase in the adjusted R 2 from 0.52 to 0.636; thus H3 was supported in the model. This implies that employees who rated high score for JC, CDP and COMM (Tomaževič et al, 2014) were more likely to be satisfied in their jobs. These findings further suggest that JS can be predicted by JC (Rathi and Lee, 2017) i.e., when employees enjoy more autonomy, skill, task variety and feedback they tend to be satisfied in their jobs.…”
Section: Hierarchical Regression Analysismentioning
confidence: 97%
“…Brayfield and Rothe (1951) defined JS as an individual's attitude toward his or her work and the net sum of the individual's positive and negative emotions experienced at work (Weiss, 2002). JS is a positive experience undergone by an employee when his expectations are met and makes him work more and better (Tomaževič et al, 2014). In the present study, the authors focused on the role of JS and defined it as "an individual's attitude toward his or her work and the net sum of the individual's positive and negative emotions experienced at work" (Brayfield and Rothe, 1951).…”
Section: Rationale For Identifying the Enablersmentioning
confidence: 98%